"y''+y'-2y=-6 \\sin 2x -18 \\cos 2x"
Above equation is second order linear nonhomogeneous differential equation with constant coefficients. The general solution of this nonhomogeneous equation is the sum of the general solution "y_0 (x)" of the related homogeneous equation ("y''+y'-2y=0") and a particular solution "y_1(x)" of the nonhomogeneous equation:
"y(x)=y_0(x)+y_1(x)".
The characteristic equation is:
"k^2+k-2=0"
Roots of this equation is "k_1=1" and "k_2=-2", so general solution of the related homogeneous equation is "y_0 (x)=C_1e^x+C_2e^{-2x}".
Let's use method of undetermined coefficient for obtaining of the particular solution of the nonhomogeneous equation "y_1(x)=A \\sin 2x +B \\cos 2x".
Differentials:
"y_1'(x)=2A \\cos 2x -2B \\sin 2x"
"y_1''(x)=-4A \\sin 2x -4B \\cos 2x"
Substitute obtained functions into the initial equation:
"-4A \\sin 2x -4B \\cos 2x+2A \\cos 2x -2B \\sin 2x-2(A \\sin 2x +B \\cos 2x)=-6 \\sin 2x -18 \\cos 2x"
"-4A \\sin 2x -4B \\cos 2x+2A \\cos 2x -2B \\sin 2x-2A \\sin 2x -2B \\cos 2x=-6 \\sin 2x -18 \\cos 2x"
"\\sin 2x (-4A-2B-2A)+ \\cos 2x (-4B +2A -2B)=-6 \\sin 2x -18 \\cos 2x"
"\\sin 2x (-6A-2B)+ \\cos 2x (2A-6B)=-6 \\sin 2x -18 \\cos 2x"
"\\begin{cases}\n-6A-2B=-6 \\\\\n2A-6B=-18\n\\end{cases}"
"\\begin{cases}\n-6A-2B=-6 \\\\\n6A-18B=-54\n\\end{cases}"
"-20B=-60"
"B=3"
"2A-6 \\cdot 3=-18"
"2A-18=-18"
"A=0"
So, "y_1(x)=3 \\cos 2x" and "y(x)=C_1e^x+C_2e^{-2x}+3 \\cos 2x".
According to the initial value problem:
"y'(x)=C_1e^x-2C_2e^{-2x}-6 \\sin 2x"
"\\begin{cases}\nC_1e^0+C_2e^0+3 \\cos 0=2 \\\\\nC_1e^0-2C_2e^0-6 \\sin 0=2\n\\end{cases}"
"\\begin{cases}\nC_1+C_2+3 =2 \\\\\nC_1-2C_2=2\n\\end{cases}"
"\\begin{cases}\nC_1+C_2 =-1 \\\\\nC_1-2C_2=2\n\\end{cases}"
"3C_2=-3"
"C_2=-1"
"C_1-1 =-1"
"C_1=0"
Finally, "y(x)=-e^{-2x}+3 \\cos 2x"
Comments
Leave a comment